A clean approach for potential continuous mass production of high-molecular-weight polylactide fibers with fully stereo-complexed crystallites. (1st March 2018) - Pan, Gangwei; Xu, Helan; Mu, Bingnan; Ma, Bomou; Yang, Yiqi
Abstract: A clean and cost-effective method for 100% stereo-complexation in polylactide (PLA) fibers with molecular weight (MW) as high as 6 × 10 5 demonstrates good potential for industrial-scale continuous manufacture. Polylactide, a widely recognized biodegradable and renewable biopolymer, has a negligible share of plastic markets due to its poor hydrolytic and thermal resistance. Stereo-complexation is effective in overcoming these challenges. However, current stereo-complexation approaches usually require solvents and/or external nucleation reagents, and are expensive and complicated. Moreover, high-MW PLAs favored for developing durable products are difficult to be stereo-complexed. In this research, enantiomeric PLAs both with MW up to 6 × 10 5 were completely stereo-complexed via a facile thermal treatment on pilot-scale devices. Neither solvent nor nucleation agent was used. For poly(L-lactide) (PLLA) fibers with MW of 6 × 10 5, percentage retention of MW and percentage retention of tensile strength after hydrolysis under simulated textile dyeing condition increased from 39% to 93% and from 20% to 89%, respectively, after complete stereo-complexation. The melting point, softening point and percentage retention of MW after hydrolysis of stereo-complexed PLA (sc-PLA) fibers were up to 51 °C, up to 59 °C and up to 183% higher than that of PLLA fibers with the same MW, respectively. The mechanism of thorough stereo-complexation in high-MW PLA fibers was proposed and verified. It is promising to use this approach to broaden industrial applications of renewable and degradable biopolymers for sustainable development of material industries. Graphical abstract: Image Highlights: A clean method for complete stereocomplexation (sc) in PLA fiber (MW up to 6 × 10 5 ) was proposed. The method shows potential for industrial continuous production of PLA products. Relationships between MW and tensile/thermal/hydrolytic properties of sc-PLA fibers were investigated. Sc-PLA fibers had softening point and MW retention rose by up to 59 °C and up to 183%. The thermally and hydrolytically stable fibers could be processed on industrial scale.